Microstructure and properties of TiB2–TiB reinforced titanium matrix composite coating by laser cladding. (November 2016) - Lin, Yinghua; Yao, Jianhua; Lei, Yongping; Fu, Hanguang; Wang, Liang
Abstract: TiB2 particle and TiB short fiber reinforced titanium matrix composite coatings were prepared utilizing in situ synthesized technique by laser cladding on the surface of Ti6Al4V alloy. Through the experiment, it was found that the surface of the single-track coatings appeared in the depression, but it can be improved by laser track overlapping. With the increase of laser power density, the amount of TiB short fiber was increased, and the distribution of TiB2 and TiB became more uniform from the top to bottom. The micro-hardness of TiB2 /TiB coating showed a gradient decreasing trend, and the average micro-hardness of the coatings was two-fold higher than that of the substrate. Due to the strengthening effect of TiB2 particle and TiB short fiber, the wear volume loss of the center of the coating was approximately 30% less than that of the Ti–6Al–4V substrate, and the wear mechanism of the coating was mild fatigue particle detachment. Highlights: Laser energy density affects the amount and distribution of TiB2 and TiB. The distribution of TiB2 and TiB causes the gradient change of micro-hardness. Composite strengthening of TiB2 and TiB causes tortuous crack propagation.